Crack of a helicopter main rotor actuator attachment: failure analysis and lessons learned - L. Allegrucci; F. De Paolis; A. Coletta; M. Bernabei (Fracture and Structural Integrity)
A Light Utility Helicopter (LUH), in the course of a training flight, leaving the ground during the taxi to take off, went into an uncontrolled rolling to the right; consequently the helicopter gradually laid down on the right side. The impact with the runway destroyed the rotating blades up to the hubs rotor. The accident investigation focused on main rotor oscillatory plate servo actuators . These components, directly linked to the cloche movements, regulate main rotor blades plane tilt and pitch. Following the preliminary examination, only front servo actuator attachment was found to be broken in two parts. In detail, the present paper deals with the fracture analysis results. The servo actuator attachment material is a 2014 Aluminum alloy extrudate,  undergone to T651 heat treatment. Fracture surfaces were examined by optical and electronic microscopy in order to determine the main morphological features and consequently to trace the origin of failure mechanism and causes. The accordance with the specification requirements about alloy composition was verified by quantitative elementary analysis through inductive coupled plasma spectroscopy (ICP); furthermore, semi-quantitative elementary analysis was locally verified by Energy dispersion spectroscopy X ray (EDS_RX). Finally, the hydrogen content of the material was evaluated by the total hydrogen analysis. Microstructural and technological alloy characteristics were verified as well by using metallographic microscopy and hardness testing of the material. Macroscopic fracture surfaces evidences were characterized by the lack of any significant plastic deformations and by the presence of symmetry compared to the servo actuator axis. Microscopic fracture features of both the investigated surfaces were not coherent to the hypothesis of an impact of the main rotor to the soil. Further achieved evidences, such as grain boundary fracture propagation, the presence of corrosion products, were all in accordance with a Stress Corrosion Cracking (SCC) progressive fracture mechanism. Finite Element Analysis (FEA) located the highest tensile stress value, when the servo actuator is in its nominal working condition, at the same points where the corrosion products were more concentrated (i.e. in the part of the fracture exposed to oxidative air effect for the longest time). The good agreement between FEA and morphological evidences allowed to determine the progressive fracture origin area, though it was not possible to individuate the crack initiation point. In fact, in correspondence to the initiation area of both the fracture surfaces, shining and flat morphology was found; then there were evidence of plastic deformations, due to the detachment of a servo actuator part.